2018
DOI: 10.1534/g3.118.200181
|View full text |Cite
|
Sign up to set email alerts
|

Tight Regulation of Srs2 Helicase Activity Is Crucial for Proper Functioning of DNA Repair Mechanisms

Abstract: Proper DNA damage repair is one of the most vital and fundamental functions of every cell. Several different repair mechanisms exist to deal with various types of DNA damage, in various stages of the cell cycle and under different conditions. Homologous recombination is one of the most important repair mechanisms in all organisms. Srs2, a regulator of homologous recombination, is a DNA helicase involved in DNA repair, cell cycle progression and genome integrity. Srs2 can remove Rad51 from ssDNA, and is thought… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 81 publications
3
12
0
Order By: Relevance
“…Several studies have shown that Tid1 is differently expressed in haploid and diploid cells (Bronstein et al, 2018;de Godoy et al, 2008;Galitski et al, 1999). We confirmed this differential expression by comparing the Tid1 protein levels in haploid and diploid cells (Figure 3A, 3B).…”
Section: Differential Tid1 Abundance Between Haploid and Diploid Cellsupporting
confidence: 82%
“…Several studies have shown that Tid1 is differently expressed in haploid and diploid cells (Bronstein et al, 2018;de Godoy et al, 2008;Galitski et al, 1999). We confirmed this differential expression by comparing the Tid1 protein levels in haploid and diploid cells (Figure 3A, 3B).…”
Section: Differential Tid1 Abundance Between Haploid and Diploid Cellsupporting
confidence: 82%
“…Δ srs2 mutants are more sensitive to DNA damage as diploid cells than as haploid cells. Consistent with a more central role of HR repair in diploids ( 34 , 45 ), Δsrs2 diploids are more sensitive to the DSB-forming agent zeocin. We show that, in contrast, a diploid strain homozygous for the srs2 ( 1-850 ) allele is as proficient as the wt parent for growth in the presence of DNA-damaging agents, with the possible exception of MMS, where a barely detected defect can be seen ( Fig.…”
Section: Resultsmentioning
confidence: 55%
“…Although many times described as an “antirecombinase,” Srs2 is essential for DSB repair by HR ( 27 ); thus, its activity is both pro- and antirecombinational ( 44 ). Moreover, even Srs2 alleles that lack the region required for interactions with Rad51 or PCNA (or with any of the proven Srs2 interactors) are still proficient in promoting synthesis-dependent strand annealing (SDSA) over crossover resolution ( 79 ) and perfectly complement the sensitivity of Δsrs2 mutants to DNA damage ( 34 , 37 , 38 , 80 this work). The new srs2 allele [ srs2 ( 1-850 )], which lacks the entire C terminus and has only the DNA helicase domain ( 15 ), is unable to interact with Rad51 ( 15 ) or with any of the known partners of Srs2 (PCNA, Rad51, Nej1, Mre11, Sgs1, Esc2, Ubc9, Siz1, Siz2, Mus81, Rad5, and Rad18 [ 23 , 40 44 ]).…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations